Odobenus rosmarus subsp. divergens Illiger 1815 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Odobenus rosmarus subsp. divergens Illiger 1815 Synonyms: Odobenus rosmarus subsp. cookii (Fremery 1831); Odobenus rosmarus subsp. orientalis (Dybowski 1922). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 595, DOI: 10.5281/zenodo.7316519